A Review on Bamboo as Natural Reinforcement in Concrete - SAADUN, SYAZWANI; A. MAJID , MASNI (Recent Trends in Civil Engineering and Built Environment, 2023)
Fibres are mainly used as a natural reinforcement in concrete. Bamboo needed quite some time before used and strong in strength. The cons properties of bamboo are easy attack by insects, fungi and high in water absorption. Bamboo must be treated to ensure the longevity of bamboo. Therefore, this study was about to investigate the physical and mechanical properties of concrete containing bamboo as a natural reinforcement compared to standard mild steel. The design addition of bamboo fibres with treated or untreated which 0.5%, 1.0%, 1.5% and 2.0% was evaluated. Overall, the bamboo fibres as reinforced concrete for 1.0% to 1.5% are the best ratio of mix designation that have significant increase in compressive and tensile strength that tested after 28 days of curing. Meanwhile, the density test for concrete is shown lower compared to mild steel fibres reinforced concrete. Treated bamboo by using chemical treatment improved strength and reduced water absorption more than 50% compared to untreated. Bamboo as reinforces in concrete are suitable for lightweight construction building.